2020
DOI: 10.1002/ppul.25166
|View full text |Cite
|
Sign up to set email alerts
|

Childhood bronchiolitis obliterans in Hong Kong‐case series over a 20‐year period

Abstract: Background and Objective: Bronchiolitis obliterans (BO) is a rare but serious condition. The natural history and outcomes remain poorly understood. In this clinical review, we aimed to describe the clinical characteristics and outcomes of children diagnosed with BO in Hong Kong (HK). Methods: This was a retrospective study of pediatric patients with BO under the care of six respiratory units in HK from January 1996 to December 2015. Information was retrieved from medical records. Results: Fifty-six patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Huang calculated that the median age of the 56 children with PIBO was 17.71 (7–91) months ( 23 ). Hong Kong’s 20-year single-center research data show that the median age at diagnosis was 1.39 years (IQR: 0.84–4.99 years), 26 patients were included with a male predominance (72.2%) ( 24 ). Our meta-analysis showed that younger children and males were at higher risk of PIBO than older children.…”
Section: Discussionmentioning
confidence: 99%
“…Huang calculated that the median age of the 56 children with PIBO was 17.71 (7–91) months ( 23 ). Hong Kong’s 20-year single-center research data show that the median age at diagnosis was 1.39 years (IQR: 0.84–4.99 years), 26 patients were included with a male predominance (72.2%) ( 24 ). Our meta-analysis showed that younger children and males were at higher risk of PIBO than older children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that patients with PIBO with the positive bronchial dilation test are not significantly associated with a family history of asthma or allergy ( 26 , 27 ). However, some studies have found that more than 50% of patients with PIBO have allergies, and this study suggested that PIBO can coexist with bronchial asthma ( 28 , 29 ). It is difficult to say whether this was a concomitant allergy or a specific symptom of PIBO.…”
Section: Discussionmentioning
confidence: 64%
“…At present, the mechanism of airway hyperreactivity in patients with PIBO is not clear. Some scholars found that patients with high airway reactivity were more likely to suffer from PIBO, and positive bronchodilation may occur in the later phase of the disease ( 27 , 29 ); or whether it was related to repeated inflammatory stimulation and airway repair, promoting the formation of airway hyperresponsiveness. However, it should be noted that a study found that airway hyperresponsiveness in PIBO was different from that caused by eosinophilic or atopic airway inflammation in patients with asthma ( 30 ), and the specific pathogenesis is needed to be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that co-infection is less severe than a single infection and even beneficial, possibly due to viral competition for resources [72][73][74][75]. On the contrary, other studies have reported the association between co-infection and severe disease outcomes including pediatric intensive care unit (PICU) admission [15,[76][77][78]. Despite the controversy, it is evident that drugs targeting multipathogens during viral co-infections should be beneficial for respiratory illness control.…”
Section: Discussionmentioning
confidence: 99%